Database optimization for improved system performance and response time of hospital management information system - Rahayudi, Bayu; Priandani, Nurizal Dwi; Hanggara , Buce Trias; Mahmudy, Wayan Firdaus (Bulletin of Social Informatics Theory and Application, 2021)
A Regional Hospital in East Java has implemented a Hospital Management Information System, namely SIMRS, in their data management system but has experienced problems in the form of slow system response when accessed by many users, was experienced in the last years when the system had been running for four years since 2016. The system’s slow response causes hospital services to be disrupted and also the quality of service to decline. So, an analysis to the existing database system is carried out, which includes an analysis of the system‘s database performance. Since many SIMRS use database servers on their data processing, then their applications will be based on executing queries and stored procedures (most of the queries are stored in stored procedures). So that, analysis of those queries will be carried out. The optimization process will include analyzing and mapping the database’s queries, profiling, and analyzing the Actual Execution Plan. By doing so, it is known which parts of the query are causing a decrease in performance and time system response. Based on the analysis results, recommendations are given for improving and rewriting several stored procedures and query statements, and the system response time is getting better.